Development and implementation of a rehabilitation triage algorithm for disasters in the subacute phase: an experience from the 2024 Noto peninsula earthquake - Shiota, Shigehito; Orita, Naoya; Tsubakita, Yuma; Ichimoto, Masaya; Shimada, Noboru; Goto, Naoya; Hirota, Tomohiro; Taito, Shunsuke; Hirata, Kazuhiko; Mikami, Yukio (Frontiers in Disaster and Emergency Medicine, 2024)
Early rehabilitation during disasters such as earthquakes is an important but often undervalued responsibility of medical teams. Both the development of simple tools for assessing the life functioning of evacuees and the standardisation of intervention methods are urgent issues in disaster rehabilitation. The Japanese Rehabilitation Assistance Team (JRAT), an officially recognised organisation consisting of 10 suborganisations, was established after gaining important experience with disaster rehabilitation in the aftermath of the Great East Japan Earthquake. We, the Hiroshima JRAT, were dispatched to the Monzen area of Wajima City to support disaster recovery after the 2024 Noto Peninsula Earthquake. Since disaster rehabilitation assistance was not well established in the Monzen area of Wajima City, the medical team consulted JRAT for guidance on triaging evacuees based on their life functioning. We developed a rehabilitation triage algorithm that classifies evacuees into four triage tags based on their ability to perform three simple movements: sitting up, standing up from the floor, and one-leg standing. In our triage algorithm, an inability to sit up is classified as a red tag (difficulty living in a shelter without assistance), an inability to stand up from the floor is classified as a yellow tag (individual intervention: introduction of beds and handrails), one-leg standing for less than 2 s is classified as a green tag (group intervention: installation of toilets and bath rails and use of walkers to prevent falls), and standing on one leg for more than 2 s is classified as a white tag (independent in ADLs). We worked with medical teams to triage 922 evacuees in 27 evacuation centres, resulting in the extraction of four red and eight yellow evacuees in one day. Our rehabilitation triage system has the potential to be a simple assessment tool for classifying the life functioning of disaster victims and linking them to appropriate supports.